2011
DOI: 10.1002/ijc.26075
|View full text |Cite
|
Sign up to set email alerts
|

Hemin, an iron‐binding porphyrin, inhibits HIF‐1α induction through its binding with heat shock protein 90

Abstract: Hypoxia and growth factor stimulation induce hypoxia-inducible factor-1a (HIF-1a), conferring upon cancer cells the ability to adapt to microenvironments and enhance proliferation, angiogenesis and metastasis. Hemin, an iron-binding porphyrin, has been used to treat porphyria attacks, particularly in acute intermittent porphyria. Although the anti-inflammatory and antitumor effects of hemin were reported, no information is available regarding its effect on HIF-1a. Our study investigated whether hemin and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Inhibitors of Hsp90 activity such as geldanamycin in HMEC-1 cells and the monkey kidney fibroblast cell line COS-7 [134] and Radicicol also affect HRE binding by the HIF-1a and HIF-1b heterodimer [81]. In addition, the iron-binding porphyrin hemin inhibits HIF-1a-dependent gene transactivation through its binding with Hsp90 in HCT116 cells [135]. The metabolite actinomycin D, an inhibitor of transcription was shown to abolish hypoxia-induced HIF-1a binding activity in Hep3B cells [11].…”
Section: Hif Dna Bindingmentioning
confidence: 99%
“…Inhibitors of Hsp90 activity such as geldanamycin in HMEC-1 cells and the monkey kidney fibroblast cell line COS-7 [134] and Radicicol also affect HRE binding by the HIF-1a and HIF-1b heterodimer [81]. In addition, the iron-binding porphyrin hemin inhibits HIF-1a-dependent gene transactivation through its binding with Hsp90 in HCT116 cells [135]. The metabolite actinomycin D, an inhibitor of transcription was shown to abolish hypoxia-induced HIF-1a binding activity in Hep3B cells [11].…”
Section: Hif Dna Bindingmentioning
confidence: 99%
“…Accumulated data have shown that most HIF-1a inhibitors target HIF-1a by either promoting HIF-1a protein degradation or inhibiting its translation (26). Several agents have been described that may affect the rate of protein synthesis, including topoisomerase I (27) and II poisons (28), cyclindependent kinase (29), Hsp90 (30)(31)(32), and microtubuledisrupting agents (16). However, recent studies have suggested that levels of HIF-1a mRNA may be a limiting factor affecting protein translation when cells were incubated under a hypoxic condition (33).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is probable that a dysfunctional heme synthesis, due to a biallelic inactivation of enzymes, could play a role in initiating carcinogenesis and tumor progression [6,15,16]. Undoubtedly, further studies are needed to confirm the second-hit model in other patients, to completely understand the mechanism of HCC in AHP.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it has been shown that hemin, the oxidative form of heme, has anti-inflammatory and anti-tumorigenic effects. More specifically, protoporphyrin IX, the product of the enzymatic reaction catalyzed by PPOX, was shown to have an inhibitory effect on hypoxia inducible factor-1a (HIF-1a) [6,15]. HIF-1a activation promotes cancer progression by upregulation of target genes, which induce tumor cell proliferation [14].…”
Section: Discussionmentioning
confidence: 99%